Penerapan Metode Demonstrasi untuk Meningkatkan Hasil Belajar Materi Tajwid pada Siswa Kelas V SDN Pasirkamuning I - Maulida Hasanah; Elia Nuryatin; Muhammad Faisal Arrayyan; M. Makbul (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This project aims to enhance students' learning outcomes in Tajwid (Quran recitation) by using a demonstration technique for Grade 5 at SDN Pasirkamuning I during the 2025/2026 academic year. The used approach was action research (PTK), grounded on the Kemmis and McTaggart framework, including the phases of planning, implementation, observation, and reflection. The research was carried out across two cycles involving 28 fifth-grade pupils. Data were gathered using both qualitative and quantitative descriptive methodologies. The results demonstrate that the demonstrative style was helpful in enhancing student engagement in Tajwid courses. Students exhibited heightened engagement, enhanced self-assurance, and improved comprehension of the rules governing the reading of “nun mati” and “tanwin” via direct recitation of the Quran. The average score in the first cycle was 80, accompanied by a success rate of 81%. During the second cycle, there was an improvement in student engagement and comprehension of Tajwid content, despite a success rate of 77%. The presentation approach provides a more experiential learning opportunity, facilitating students' comprehension of abstract subjects. This method enables instructors to cultivate a more interactive and stimulating learning atmosphere. Consequently, the demonstrative method may provide as a successful tool for enhancing children's Tajwid learning results in primary education.